Circular structures on the seabed: differentiating between natural and anthropogenic origins—Examples from the Southwestern Baltic Sea - Díaz-Mendoza, Giuliana Andrea; Krämer, Knut; von Rönn, Gitta Ann; Schwarzer, Klaus; Heinrich, Christoph; Reimers, Hans-Christian; Winter, Christian (Frontiers in Earth Science, 2023)
Hydroacoustic observations of shallow marine environments reveal a variety of seafloor structures–both of natural and anthropogenic origin. Natural processes can result in features with circular geometries on the seafloor, such as kettles, sinkholes or iceberg pits, but human activities such as dredging, dumping, or detonating explosives can also cause similar shapes. Explaining the origin of these features is difficult if there are only few observations or if competing natural and anthropogenic processes have acted in the same area. Even though the location of dredging and dumping operations and munition blasting may be well documented in many parts of the global coastal ocean today, little information might be available about human practices in the past. In this study, more than 3,000 circular features were identified in side-scan sonar (SSS) datasets covering 1,549 km2 of shallow waters in the southwestern Baltic Sea. Additional data obtained by multibeam echosounder (MBES), sub-bottom profiler (SBP), and different SSS was considered in the analysis of 205 circular features that were characterized based on their sedimentology, morphology, SSS and SBP acoustic signatures. Characteristic differences between the structures allow their classification into six classes, which provide insight into their formation mechanisms. The obtained parameters (morphology, MBES and SSS acoustic backscatter, SBP characteristics and spatial distribution) allow the classification to be applied to the entire SSS dataset, resulting in the classification of 2,903 features. The mapped circular features have diameters between 6 and 77 m and correspond to pockmarks, dumping spots and explosion craters in water depths ranging from 8 m up to 25 m. Despite this rather multi-methodological approach, the origin of some observed features still cannot be explained with certainty, leaving room for further investigations of natural processes and human impacts on the seafloor.